Auditing firm reputation, ex ante uncertainty and the underpricing of initial public offerings on the second board of the Kuala Lumpur Stock Exchange: 1990-1995 - Ramadilli Mohd, Shamsher Mohamad; Md Nasir, Annuar (Universiti Putra Malaysia Press, 1997)
Reputable auditing firms have an incentive to investigate and report irregularities since their reputation is at stake, therefore engaging their services enables investors to estimate the value of the firm more precisely and reduce ex ante uncertainty. This will attract more investors to bid for the IPO shares and consequently IPOs attested by reputable auditing firms will have a lower premium level. This study tests the conjectured inverse effect of reputation of auditing firms on the level of IPO underpricing of 100 companies listed on the second board of the Kuala Lumpur Stock Exchange, for the period 1990-1995. The reputable auditing firms are the Big Six accounting firms; the others are classified as less reputable. The findings do not support this conjecture, which implies that Malaysian investors assume that all qualified and licensed auditing firms provide homogeneous services. However, the findings show that the underwriter reputation (UW) and the past profitability of the firm (NPM) variables are inversely related, whereas the market trend and the standard deviation variables are positively associated to the level of IPO underpricing.